Diagnostic Test of Frailty Syndrome Based on Scoring Systems of Cardiovascular Health Study (CHS), Study of Osteoporotic Fracture (SOF), and Tilburg Frailty Indicator (TFI) to Frailty Index Based on Comprehensive Geriatric Assessment (FI- CGA) - Widyasari, Rastita; Widajanti, Novira; Ichwani, Jusri (International Journal of Psychosocial Rehabilitation, 2020)
The Cardiovascular Health Study (CHS), Study of Osteoporotic Fracture (SOF), and Tilburg Frailty Indicator (TFI) scoring systems are known to be more applicable than Frailty Index Based on Comprehensive Geriatric Assessment (FI-CGA) in community health services but their diagnostic capabilities have not been known. The objective of this study was to find out the diagnostic test of frailty syndrome based on CHS, SOF, and TFI to FI-CGA scoring system in Surabaya elderly community. This study was a cross-sectional analytic study with diagnostic test approach that is calculating sensitivity, specificity, positive predictive value, negative predictive value, positive likelihood ratio, negative likelihood ratio, and ROC curve of CHS, SOF, and TFI to FI- CGA scoring system as reference standard. A total of 170 females and males aged >60 years who were enrolled in elderly health center in this study. To classify frail and non-frail conditions, CHS had 78.57% sensitivity, 71.8% specificity, and AUC value of 0.802 (CI=95%, p<0.001), SOF had 23.8% sensitivity, 87.5% specificity, and AUC value of 0.739 (CI=95%, p<0.001), TFI had 71.43% sensitivity, 78.13% specificity, and AUC value of 0.859 (CI=95%, p<0.001). CHS and TFI have a good diagnostic capability to diagnose frailty syndrome in health center for elderly in Surabaya.